Sharing Linked Data for Health Research: Towards Better Decision Making: Synopsis by the authors - Adams, Carolyn; Allen, Judy; Flack, Felicity (International Journal of Population Data Science, 2022)
Publication details Cambridge University Press Part of Cambridge Bioethics and Law Series June 2022 ISBN: 9781108426640 Online ISBN: 9781108675789 Price: £69.87 Intended readership The book is written for those who are involved in making decisions about collecting, linking, and using data for health research in government and in research institutes including data custodians, data linkers, members of ethics committees and privacy committees. It is also for legislators and policy makers responsible for the law and policies that regulate the use of data, and for privacy professionals and consumer advocates. The book will help researchers who use linked data understand the regulatory environment in which they operate, and the ethical and legal issues involved. The book will have broad international appeal in all countries with data linkage programs. The book contains detailed comparisons of the law and decision-making models in Australia, Canada, and the United Kingdom, but the issues and general concepts discussed in the book are internationally relevant to addressing the challenges in all jurisdictions. Overview Research using linked data has the capacity to address ‘wicked’ health problems and emerging global threats to health. Governments hold much of the most valuable, reliable, and comprehensive health data that is crucial for health research around the world. These data collections are made up of sensitive information about members of the community. While this information can be used to administer and improve health care it can also be used in illegitimate ways to profile, harm, and unjustly discriminate against individuals and groups. For this reason, the collection, use and release of the information is highly regulated. The focus of this book is on decision making. It provides a template for allowing access to government data collections for research in a regulatory environment that respects and protects the values, interests, and rights of individuals and communities and establishes and maintains the social licence needed to support the research enterprise. The book: Provides a comprehensive review of the human rights, ethical and legal decision-making frameworks that regulate the sharing of linked data for research. Includes detailed recommendations for improving the regulation of research using linked data. Compares and critiques practice and process in three jurisdictions that have well established data linkage infrastructure and programs — Australia, Canada, and the UK. Key messages Consent and anonymisation are no longer adequate to protect individual interests and they ignore collective interests. A robust authorisation and approval model is needed. Social licence is essential for the legitimacy of research using linked data without consent. Decision making principles and processes should support social licence. All relevant human rights should be recognised and considered in decisions about using health data including the right to health and the right to privacy. All individual level data is potentially identifiable and the applicable law, and the decision-making principles and processes should be the same whether it is identified, de-identified or re-identifiable. Clear separation between governance and ethics decision making is needed to ensure that the right decision makers are making decisions on the relevant criteria. There should be ethics review of all projects involving individual level data by a committee with relevant expertise and diverse perspectives applying guidelines that recognise collective interests, all relevant rights, and diverse ways of ensuring respect. Synopsis Part 1 provides the context for decision making about data linkage for research. Chapter 1 describes the ways in which linked data is being used to improve diagnosis, treatment, and healthcare delivery and to understand the drivers of health. The chapter surveys the kinds of data currently being linked for research and different linkage methods and considers the potential and challenges for future international data linkage. Chapter 2 considers the interwoven interests of individual participants, collective interests, and the wider public interests. The chapter evaluates traditional approaches to protecting the dignity, autonomy, and privacy of individuals — consent and anonymisation — and concludes that these do not provide effective protection in this context. The impacts, both beneficial and harmful on socio-demographic groups, disease groups and the wider community should also be explicitly recognised and evaluated by decision makers. The current legal and ethical regulation of data linkage research are critiqued for being too individualistic and alternative approaches are discussed. Chapter 3 examines the nature of social licence and its application to research using linked data. Social licence is framed as an analytical tool to design and evaluate decision making processes. The chapter examines the qualitative evidence of public perceptions and the conditions for community support and identifies the substantive and procedural conditions that lead to trust and legitimacy. The chapter concludes that these conditions should be embedded in the governance of research using linked data to develop and sustain community acceptance. In Part 2 the three regulatory frameworks for making decisions— human rights, research ethics, and law — are explored. Chapter 4 considers the human rights relevant to research using linked data without consent; how these rights come into tension with each other and other relevant interests; and how these tensions should be considered and resolved. It notes the emphasis placed in the West on civil and political rights, such as the right to privacy, and the lack of attention to economic, social, and cultural rights, such as the right to health, and how this has resulted in an unbalanced approach to the regulation of research. Chapter 5 describes the ethical framework regulating research using linked data and examines the applicable international ethics guidelines. A hypothetical research project is used to compare the way in which these guidelines address the ethical assessment of research using linked data. It compares how the guidelines address waiver of consent and the extent to which they consider collective interests. The chapter goes on to discuss how the core ethical values of research merit and integrity, justice, beneficence, and respect can be reinterpreted to encompass the ethical concerns raised by research using linked data. Chapter 6 considers the legal basis on which linked data is used and disclosed for research in Australian, Canada, and the United Kingdom. The chapter describes how the relevant bodies of law regulate the use of data and balance the relevant private and public interests in play. The chapter critiques these bodies of law in terms of clarity and consistency. Part 3 turns to the current decision-making practices and processes and considers how these impact on access to data for researchers and community support for research using linked data. Chapter 7 uses three case studies to describe decision making for using and sharing linked data for research in three jurisdictions: Western Australia, Scotland, and Manitoba. Each case study looks at the decision makers; the relevant law, policy, and guidelines regulating the decision-making process; and the ethical review process. The chapter assesses the practice and process in each jurisdiction against metrics of good decision making - efficiency, transparency, accountability, and community participation. Chapter 8 concludes the book by proposing ways to improve decision-making in relation to sharing linked data for research. The chapter sets out the interests, values and rights that should frame decisions in this sphere. Some of these are not currently represented in decision-making frameworks. It provides a list of decision-making criteria that should be satisfied and the considerations relevant to those criteria. The chapter discusses the role of data custodians, privacy committees and ethics committees in decision making and concludes there should be clear separation between ethical decisions and governance decisions. Finally, the chapter makes recommendations for a decision-making process that is efficient, transparent, accountable, and collaborative. These recommendations aim to ensure better decisions and that both the decision-making process and the decisions themselves develop and sustain the social licence needed to support the important enterprise of research using linked data. Webinar The authors gave a webinar introducing the main themes of the book to mark its publication. The webinar can be accessed here <a href="https://eur03.safelinks.protection.outlook.com/?url=https%3A%2F%2Fyoutu.be%2FlkjBvhEgPTU&data=05%7C01%7CN.Corlett%40Swansea.ac.uk%7C5809218e02b74590bb5108da54f644f4%7Cbbcab52e9fbe43d6a2f39f66c43df268%7C0%7C0%7C637915713929985973%7CUnknown%7CTWFpbGZsb3d8eyJWIjoiMC4wLjAwMDAiLCJQIjoiV2luMzIiLCJBTiI6Ik1haWwiLCJXVCI6Mn0%3D%7C3000%7C%7C%7C&sdata=R3LAfhmTaGyQy6e5SJfV9lOp3SQrIpybhoWSiLjEd6c%3D&reserved=0">https://youtu.be/lkjBvhEgPTU. Citation Adams, C., Allen, J., & Flack, F. (2022). Sharing Linked Data for Health Research: Toward Better Decision Making (Cambridge Bioethics and Law). Cambridge: Cambridge University Press.